2008
DOI: 10.1136/ip.2007.016832
|View full text |Cite
|
Sign up to set email alerts
|

Paraprofessional home visitation program to prevent childhood unintentional injuries in low-income communities: a cluster randomized controlled trial

Abstract: Objective: To investigate the effectiveness of a paraprofessional home visitation program (HVP) to improve home safety and prevent injuries among children living in low-income settings. Methods: The HVP was implemented in two low-income communities in South Africa. In each community, approximately 200 households were randomly selected for the trial. Eligible households were those with children aged (10 years. Intervention households received four visits, one every two weeks, by trained paraprofessionals that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 26 publications
(39 reference statements)
3
60
0
Order By: Relevance
“…Interventions promoting the use of child resistant containers (CRCs) were reported from two studies (see Table 4) included in six reviews (Elkan et al, 2000;Kendrick, Coupland et al, 2007;Lyons et al, 2006;Lyons et al, 2003;Pearson et al, 2009;Towner et al, 1996) and a further two studies not included in reviews. One RCT evaluating the effects of home visits providing safety education, home safety inspection, and provision of child proof locks and child resistant caps (CRCs) reported significantly more intervention group families stored paraffin in containers with CRCs (OR 3.39, 95% CI 1.28À9.02) (Swart et al, 2008). The remaining three 22 P.M. Wynn et al…”
Section: Interventions Promoting Use Of Child Resistantmentioning
confidence: 99%
See 3 more Smart Citations
“…Interventions promoting the use of child resistant containers (CRCs) were reported from two studies (see Table 4) included in six reviews (Elkan et al, 2000;Kendrick, Coupland et al, 2007;Lyons et al, 2006;Lyons et al, 2003;Pearson et al, 2009;Towner et al, 1996) and a further two studies not included in reviews. One RCT evaluating the effects of home visits providing safety education, home safety inspection, and provision of child proof locks and child resistant caps (CRCs) reported significantly more intervention group families stored paraffin in containers with CRCs (OR 3.39, 95% CI 1.28À9.02) (Swart et al, 2008). The remaining three 22 P.M. Wynn et al…”
Section: Interventions Promoting Use Of Child Resistantmentioning
confidence: 99%
“…Interventions to promote other poisoning prevention practices. Twelve reviews reported nine studies (see Table 4) evaluating interventions promoting other poisoning prevention practices (Elkan et al, 2000;Guyer et al, 2009;Kendrick, Coupland et al, 2007;Lyons et al, 2003Lyons et al, , 2006Nilsen, 2004;Nixon et al, 2004;Pearson et al, 2009;Spinks et al, 2004;Towner et al, 1996United States Preventive Services Task Force, 1996) as did a further four studies not included in any reviews (Kendrick Groom et al, 2007;Odendaal, van Niekerk, Jordaan, & Seedat, 2009;Reich et al, 2011;Swart et al, 2008). Of the 13 primary studies, one CBA study (Garcia, 1996) reported that the intervention group showed a significant improvement in poison safety scores after a school safety fair but no figures or p value were reported.…”
Section: Interventions To Promote Use Of Poison Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…storage of the fuel on upper shelves) and making people feel more vulnerable to the threat of injuries in their own home. 18,19 Perception of risk must be a primary target for behaviour change because people are only likely to change when they feel vulnerable. We found that those at risk for paraffin-related injury perceive some degree of risk, which is promising, although perhaps still less than the actual threat, especially for fires.…”
Section: Discussionmentioning
confidence: 99%